African-Centered Social Work in the 21st Century: A Content Analysis. Issue 1 (29th October 2022) - Lateef, Husain; Gale, Adrian; Boyd, Donte; Arab, Hassan; Amoako, Emmanuel; Williams, Ed-Dee
Abstract: Endorsement of African-centered theory and practice are widespread within Black communities across the United States. The usage of African-centered frameworks is also common among many Black social workers. However, past research suggests that African-centered theory and subsequent models of practice are marginalized within social work literature and curricula. Since advocacy began for the inclusion of African-centered approaches to practice during the mid to late 1990s, there have been no strategic analyses tracing how African-centered scholarship has advanced within social work. This study sought to examine to what extent the African-centered framework is included within scholarship among prominent social work journals. A content analysis was conducted of articles in six major social work journals published between 2000 and 2019. A total of 42 articles met the criteria for inclusion. While there has been a level of change in the number of published articles of African-centered social work, findings suggest that relative to other practice modalities/models, African-centered scholarship is noticeably lacking in social work literature. The article concludes with implications to advance culturally responsive research and practice with communities of African descent.